ANALISIS PENDAPATAN PETANI KARET DI KECAMATAN SINGINGI HILIR KABUPATEN KUANTAN SINGINGI - Atrio Andika; Hendro Ekwarso; Taryono Taryono (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2018)
This study aims to determine the costs incurred by rubber farmers in the Singingi Hilir Subdistrict of Kuantan Singingi Regency. To know the income of rubber farmers in Kecamatan Singingi Hilir Kuantan Singingi Regency.The population in this study is 2,860 households. Samples were chosen based on certain groups as targets by using the quotas assigned to the group that is rubber farmers with rubber age for 7-20 years that is as many as 43 people. Methods of data collection include interview and documentation ametode. The analysis method uses descriptive percentage. Based on the results and discussion described in chapter V then obtained some conclusions as follows: The cost of farming consisted of fixed costs and variable costs with the average total cost for rubber farming of Rp. 23,197,709 consisting of variable cost is Rp. 19.849.535. The average revenue from rubber farming in Kecamatan Singingi Hilir Kuantan Singingi Regency is Rp. 47,369,302 per year after deducting all expenses incurred to generate. So the average income of rubber farming in Kecamatan Singingi Hilir Kuantan Singingi regency of Rp.11.943.580 per year. Net income derived from gross revenues reduced by variable costs on rubber farming.Keywords : Revenue, Rubber Farmers